Nucleon Momentum Distributions and Elastic Electron Scattering form Factors for some 1p-Shell Nuclei - Hamoudi, A K; Hassan, M A; Ridha, A R (Al-Nahrain Journal of Science, 2018)
The Nucleon Momentum Distributions (NMD) and elastic electron scattering form factors of the ground state for 1p-shell nuclei with Z=N (such as 6Li, 10B, 12C and 14N nuclei ) have been calculated in the framework of the Coherent Density Fluctuation Model (CDFM) and expressed in terms of the weight function . The weight function has been expressed in terms of the Nucleon Density Distributions (NDD) of the nuclei and determined from theory and experiment. The feature of the long-tail behavior at high momentum region of the NMD’s has been obtained by both the theoretical and experimental weight functions. The experimental form factors  of all considered nuclei are very well reproduced by the present calculations throughout all values of momentum transfer . It is found that the contributions of the quadrupole form factors  in 10B and 14N nuclei, which are described by the undeformed p-shell model, are essential in obtaining a remarkable agreement between the theoretical and experimental form factors.